2009
DOI: 10.1080/00016350903160563
|View full text |Cite
|
Sign up to set email alerts
|

Caries preventive effect of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP): a meta-analysis

Abstract: Within the limitations of this systematic review with meta-analysis, the results of the clinical in situ trials indicate a short-term remineralization effect of CPP-ACP. Additionally, the promising in vivo RCT results suggest a caries-preventing effect for long-term clinical CPP-ACP use. Further randomized control trials are needed in order to confirm these initial results in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 37 publications
3
89
0
4
Order By: Relevance
“…The review of Azarpazhooh et al 7 concluded that the quality and quantity of articles reviewed were insufficient to generate conclusive evidence of the long term effectiveness of casein derivative compounds, especially CPP-ACP.…”
Section: Systematic Reviewsmentioning
confidence: 99%
See 3 more Smart Citations
“…The review of Azarpazhooh et al 7 concluded that the quality and quantity of articles reviewed were insufficient to generate conclusive evidence of the long term effectiveness of casein derivative compounds, especially CPP-ACP.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…The first of these, conducted by Azarpazhooh et al 7 , reunited randomized and quasi randomized clinical studies, published up to October 2007, which tested the efficacy of casein derivatives (among them CPP-ACP) in the diverse forms of dental application.…”
Section: Systematic Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent meta-analysis study carried out by Yengopal and Mickenautsch, (2009) to investigate whether CPP-ACP has any superior caries-preventive benefit over any other intervention or placebo.…”
Section: Acp)mentioning
confidence: 99%